Renewable Energy Sources and Their Impact on Electricity Production in the EU - ANGHELUȚĂ, Petrică Sorin; NICA, Elvira; DUMITRESCU, Oana Cătălina; GRĂTIANU, Emil (European Journal of Sustainable Development, 2025)
Increasingly often, certain changes in the energy sector appear as a necessity. The purpose of these changes is given by both the desire to improve energy security and to mitigate climate change. One of the solutions for reducing greenhouse gas emissions is the use of renewable energy sources. Both energy production and consumption are important. Thus, the article presents an analysis of gross electricity production, as well as gross final energy consumption. For this reason, energy productivity is analyzed by presenting its evolution. For a transition to clean energy, renewable energy sources can replace fossil fuels. Thus, the use of renewable energy sources can constitute an alternative to the use of fossil fuels. Energy systems that have low carbon emissions allow for the reduction of pollution and increase energy security. Considering the main renewable sources, a comparative situation of electricity production capacities is presented for the period 2013-2023. Keywords: renewable sources, gross electricity production, European Union